Living documentation : continuous knowledge sharing by design - Martraire, Cyrille (Addison-Wesley, 2019)
Use an Approach Inspired by Domain-Driven Design to Build Documentation That Evolves to Maximize Value Throughout Your Development Lifecycle Software documentation can come to life, stay dynamic, and actually help you build better software. Writing for developers, coding architects, and other software professionals, Living Documentation shows how to create documentation that evolves throughout your entire design and development lifecycle. Through patterns, clarifying illustrations, and concrete examples, Cyrille Martraire demonstrates how to use well-crafted artifacts and automation to dramatically improve the value of documentation at minimal extra cost. Whatever your domain, language, or technologies, you don't have to choose between working software and comprehensive, high-quality documentation: you can have both . · Extract and augment available knowledge, and make it useful through living curation · Automate the creation of documentation and diagrams that evolve as knowledge changes · Use development tools to refactor documentation · Leverage documentation to improve software designs · Introduce living documentation to new and legacy environments.